Grain Sorghum Cost-Return Budget in North Central Kansas - Dhuyvetter, Kevin C. (My University, 1999)
This publication provides estimated cost and returns for forward farm planning for grain sorghum in north central Kansas.
MF2159_1999_10
Keywords: MF2159; Crops; Economics; MF